Pengaruh Pengetahuan Dan Lokasi Terhadap Minat Menabung Pada Masyarakat Desa Jentera (Studi Kasus Bank Muamalat KCP Stabat) - Yunita, Dina Rizky; Hasanah, Uswah (Jurnal Manajemen Akuntansi (JUMSI), 2023)
This research was conducted with the aim of analyzing the effect of the knowledge and location of the Jentera Village community on the interest in saving at the Muamalat KCP Stabat bank. The research method used in this study is quantitative research and data collection techniques in this study using a questionnaire. The data analysis used in this research is data quality test, classic assumption test, multiple linear regression test, hypothesis test, and determination test. Based on the results of the study, it showed that the Knowledge Variable (X1) had a positive and significant influence on the Interest in Saving Variable (Y) with tcount (18.949) > ttable (1.997) with a significant value of 0.001 <0.05, Location Variable (X2) had a positive and significant to Saving Interest Variable (Y) with the acquisition of tcount (6.942) > ttable (1.997) with a significant value of 0.001 <0.05, simultaneous tests on Knowledge Variables (X1), and Location (X2) state that there is a jointly significant influence - the same as Interest in Saving (Y) with the acquisition of Fcount (186.826) > Ftable (3.14) with a significant level of 0.001.